The EU-Africa summit 2021 : Quo vadis, in the light of Brexit and Corona ? - Kohnert, Dirk (My University, 2021)
Every three years, the AU-EU summit reunites African and EU leaders to outline the future direction of cooperation. The 6th summit had been to reaffirm and renew the partnership between the two blocks already in October 2020, but it was pushed back to the first quarter of 2021 or even later due to COVID-19 crisis. Besides, Brussels had to deal with its own post-Brexit situation and its repercussions on EU-Africa relations, excluding the UK. African states, for their part, wanted to renegotiate the EU-Africa partnership and to balance it with new promising Post-Brexit visions of the British premier Johnson about increased economic ties with the African Angloshere. China and other global players compete with the EU and its member states in the new scramble for African resources. Given that Africa is increasingly courted by other partners it could be inclined to successively limit its relations with the EU and see it as a mere provider of aid and security against Islamic terrorism. This trend was reinforced by the fact that the new EU-Africa strategy still hasn't been approved by EU member states. And a timely replacement of the Cotonou Agreement, which expires in November 2021, is open to question.
Keywords: Africa; African Studies; Brexit; Corona; Covid-19; EU; EU-Africa summit